SIGNS OF CONSUMERISM IN THE INVESTMENT ACTIVITIES OF JOINT STOCK COMPANIES - Herasymova, S. V. (Science and Transport Progress, 2006)
Such category as «economic interest» is examined as an element of consumerism. The accent is made on the economic interests which are pursued by the subjects of a joint-stock company during realization of investment activity. In relation to harmonization of these interests, there have been proposed specific administrative actions, with account of the other identifying signs of consumerism.